2003
DOI: 10.1074/jbc.m301397200
|View full text |Cite
|
Sign up to set email alerts
|

A Carboxyl-terminal Mutation of the Epidermal Growth Factor Receptor Alters Tyrosine Kinase Activity and Substrate Specificity as Measured by a Fluorescence Polarization Assay

Abstract: The expression of certain COOH-terminal truncation mutants of the epidermal growth factor receptor (EGFR) can lead to cell transformation, and with ligand stimulation, a broader spectrum of phosphorylated proteins appears compared with EGF-treated cells expressing wild-type EGFR. Accordingly, it has been proposed that elements within the COOH terminus may determine substrate specificity of the EGFR tyrosine kinase (Decker, S. J., Alexander, C., and Habib, T. Our data demonstrate that the steady-state kinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This translates to a k cat value of r10 À6 s À1 or a reduction by at least a factor of 10 À6 relative to the experimental k cat value of the EGF activated receptor or a factor of 10 À5 relative to the experimental k cat value in the absence of EGF. 54,58,59,62,63 The reduction in k cat manifests itself as little or very weak residual activity through pathway II, which is consistent with recent experiments. 64,65 Given that the protonation states of titratable side-chains in the active site can have a considerable effect on the stability of the ground state as well as on the energies of the reaction landscape, we explored the different protonation states of the conserved catalytic residue D813 in EGFR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This translates to a k cat value of r10 À6 s À1 or a reduction by at least a factor of 10 À6 relative to the experimental k cat value of the EGF activated receptor or a factor of 10 À5 relative to the experimental k cat value in the absence of EGF. 54,58,59,62,63 The reduction in k cat manifests itself as little or very weak residual activity through pathway II, which is consistent with recent experiments. 64,65 Given that the protonation states of titratable side-chains in the active site can have a considerable effect on the stability of the ground state as well as on the energies of the reaction landscape, we explored the different protonation states of the conserved catalytic residue D813 in EGFR.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it has been suggested that protein tyrosine kinase (including EGFR) select substrates with glutamic acid at the P À 1 position and large hydrophobic amino acids at the P + 1 position. [22][23][24][25]54,58,59 Our predicted peptide bound ternary complex suggests that a highly conserved region, corresponding to Val852-Pro853-Ile854-Lys855-Trp856 in EGFR TKD is essential for substrate binding: Lys855 forms a salt bridge with the highly preferred glutamic acid residue at the P À 1 site, and the hydrophobic pocket formed by Val852, Pro853, Ile854 and Trp856 serves to anchor a large hydrophobic residue at the P + 1 position. This observed binding mode for our top-ranked configuration is consistent with the hypothesis that the substrate-binding surface formed through hydrophobic contacts and hydrogen bonds help orient the tyrosine residue for catalysis.…”
Section: Discussionmentioning
confidence: 89%
“…This evidence strongly suggests the contribution of some extrinsic factors that need to be modeled, such as unknown kinase inhibitors like Mig6 [53], [54], or the alteration of the substrate specificity of EGFR caused by the mutation [55]. An alternative possibility could be the involvement of SFKs that are highly associated with EGF-induced tyrosine phosphoproteome [45].…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, dysregulation of receptor degradation could be one of the possible oncogenic mechanisms of EGFR CTD deletion mutant, which is consistent with previous reports (42, 43). In addition, the CTD deletion mutants may have altered EGFR substrate specificity/receptor degradation or no longer bind regulatory proteins including Mig6 which has been found to negatively regulate EGFR kinase activity by blocking the activating dimer interface (44-46). Further experiments are needed to test these possibilities and to characterize a detailed mechanism of oncogenic activation of EGFR CTD deletion mutants.…”
Section: Discussionmentioning
confidence: 99%